Dissemination of information on natural rubber by the Rubber Research Institute of India: Scientific books - Thomas K K (Rubber Board Bulletin, 2006)
The paper evaluates the contributions of Rubber Research Institute of India (RRII) towards the dissemination of information through scientific books. Ever since the publication of the first book in 1977, RRII has released 20 books of which six are proceedings of conferences organized or hosted by the Institute. Publication of Handbook of Natural Rubber Production in India in 1980 and Natural Rubber: Agromanagement and Crop Processing in 2000 is a landmark in the annals of NR in India. Two books of the Institute were published by overseas publishers, five by Indian publishers and the remaining 13 were brought out by the Institute itself. RRII published 11 books since 2001 of which seven were released in 2005-2006 in commemoraiton of the Golden Jubilee of the Institute.
Keywords: Books; India; Information dissemination; NR; Publications; RRII